THE ROLE OF TEACHERS IN INTEGRATED SOCIAL STUDIES LEARNING AT SMP NEGERI 1 BOTUPINGGE - Nabu, Fatria; Yunus, Resmiyati; Mondong, Tonny Iskandar (Satmata: Journal of Historical Education Studies, 2024)
The aim of this study is to develop students' potential to be more sensitive to social issues occurring in society and to foster a positive attitude toward addressing existing inequalities. The research method employed is qualitative. The findings indicate that by observing the learning process in the eighth-grade classroom, it was evident that the learning process was less effective. This was influenced by the teacher's lack of firmness in handling students who frequently caused disturbances in class. Effective learning is closely related to the teacher's ability to manage the classroom optimally so that both students and learning resources can contribute to an effective learning process. The study concludes that the high discrepancy in the ability of social studies teachers in junior high schools to elaborate on the subject competencies is due to their educational background, which is based on specific branches of science.